A critical analysis regarding Diomedes and the communication of ‘menos’ (Iliad, Book V) - Rodrigues, Eduardo (Romanitas - Revista de Estudos Grecolatinos, 2026)
Abstract: This article proposes a critical analysis of the definition of “communication of menos” as presented by Maria Daraki (1980). This concept refers to moments when a god transmits ‘ardour’ to a hero, often accompanied by a poetic formulaic description in which the deity ‘softens’ the hero’s limbs, making them lighter. Our central hypothesis is that Daraki’s definition presents descriptive limitations, preventing the identification of all instances in which menos is transmitted from a deity to a human in the Iliad. To support this analysis, we divide the study into two main stages. First, we address the definition of menos, considering contemporary etymological and terminological studies. Then, we examine the occurrences of the term menos in the first five books of the Iliad, with particular attention to the aristeia of Diomedes (Il. V).
Keywords: Iliad; Warrior fury; Menos; Divine Communication